Dielectric and conduction mechanism studies of PVA-orthophosphoric acid polymer electrolyte - Majid, Siti Rohana; Arof, Abdul Kariem; Kufian, M.Z. (Springer Verlag (Germany), 2007)
Polyvinyl alcohol (PVA)-based proton conducting polymer electrolytes have been prepared by the solution cast technique. The conductivity is observed to increase from 10(-9) to 10(-4) S cm(-1) as a result of orthophosphoric acid (H3PO4) addition. The plot of conductivity vs temperature shows that a phase transition occurred at 343 K in the sample PVA-33 wt% H3PO4. The beta-relaxation peak is observed at 313 K. The glass transition temperature of PVA-33 wt% H3PO4 is 343 K. Orthophosphoric acid seems to play a dual role, i.e., as a proton source and as a plasticizer. The ac conductivity sigma(ac) = A omega(s) was also calculated in the temperature range from 303 to 353 K. The conduction mechanism was inferred by plotting the graph of s vs T from which the conduction mechanism for sample PVA-17 wt% H3PO4 was inferred to occur by way of the overlapping large polaron tunneling (OLPT) model and the conduction mechanism for the sample PVA-33 wt% H3PO4 b,y way ol thc correlated barrier height (CBH) model.